2017
DOI: 10.3233/jad-170218
|View full text |Cite
|
Sign up to set email alerts
|

An Intracellular Amyloid-β/AβPP Epitope Correlates with Neurodegeneration in those Neuronal Populations Early Involved in Alzheimer’s Disease

Abstract: The main histopathological hallmarks of Alzheimer's disease (AD) are the extracellular deposition of neuritic amyloid plaques, composed of amyloid-β (Aβ) peptide, and the intracellular accumulation of neurofibrillary tangles, composed of hyperphosphorylated tau. Both traits are emulated in the 3xTg-AD mouse model. Because the relevance of this model in the bibliography and the main role of Aβ in neuronal impairment, here we have detailed the brain Aβ/AβPP distribution to subsequently quantify cellular density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
4
9
0
Order By: Relevance
“…This early volume variation might be related with intracellular Aβ accumulation, which is already described at 2–3‐mo in this model . Moreover, we recently described the existence of a direct relationship between the amount of intracellular Aβ peptide and cell death in several affected neuronal populations at 5‐mo and the mechanism by which scFv‐h3D6 protects these neurons from demise . In this study, the volume results are compatible with histological and biochemical analyses, as 3xTg‐AD mice showed an evident development of Aβ pathology.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This early volume variation might be related with intracellular Aβ accumulation, which is already described at 2–3‐mo in this model . Moreover, we recently described the existence of a direct relationship between the amount of intracellular Aβ peptide and cell death in several affected neuronal populations at 5‐mo and the mechanism by which scFv‐h3D6 protects these neurons from demise . In this study, the volume results are compatible with histological and biochemical analyses, as 3xTg‐AD mice showed an evident development of Aβ pathology.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, the brains were completely embedded in paraffin. The brain samples ( N = 4) were serially sectioned in the coronal plane (10‐μm sections) and stained either by immunohistochemistry or by immunofluorescence as previously described . The primary antibodies used were 6E10 Mouse anti‐amyloid‐β (1‐16) (bioLegend®, San Diego, California, USA) and rabbit polyclonal anti‐NeuN (Merck‐Millipore, Billerica, MA, USA), both at 1:100, while the secondary antibodies used were goat anti‐mouse IgG Cy3 conjugated (Chemicon, Merck‐Millipore) and goat anti‐rabbit IgG (H + L) Alexa Fluor 488 (Abcam, Cambridge, UK), both at 1:200, for immunofluorescence, and goat anti‐mouse conjugated to biotin (Sigma, Saint Louis, MO, USA) and mouse extravidin peroxidase conjugate (Sigma), both at 1:50, and DAB solution for immunochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…At 9 months of age, diffuse amyloid plaques in the subiculum of 3xTg-AD and intraneuronal Aβ pathology, mainly in the CA1 of the hippocampus, could be clearly seen ( Figure 7 A). As a reference, only intraneuronal Aβ pathology in the hippocampus was reported at 5 months of age [ 53 ]. In addition, total tau staining was also evident in 9-month-old 3xTg-AD mice.…”
Section: Resultsmentioning
confidence: 99%
“…Aβ excessive formation and blocked degradation impel SP deposition in the brain that, subsequently, accelerate the occurrence of overactive microglia, excessive apoptotic neurons and cerebral atrophy (Selkoe and Hardy, 2016;Nixon, 2017). In recent years, it has been found that extracellular Aβ is only the result of its toxic effect on cells, and the accumulation of intracellular Aβ is the fundamental factor leading to the cytotoxic effects (Esquerda-Canals et al, 2017). The degradation of extracellular Aβ is mainly completed by the insulin-degrading enzyme (IDE) and enkephalinase (Yamamoto et al, 2013(Yamamoto et al, , 2014, while the degradation of intracellular Aβ is mainly transported to lysosome through endocytosis or autophagy (Thal, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of AD, the clearance of Aβ decreased due to the fusion of APs and lysosomes. The accumulation of APs due to the inhibition of degradation led to the further increase of Aβ production (De Strooper and Karran, 2016;Esquerda-Canals et al, 2017). So it has been reported that autophagy acts as a ''double-edged sword'' in the development of AD (Martinet et al, 2009;Choi et al, 2018;Hamano et al, 2018).…”
Section: Introductionmentioning
confidence: 99%